2016
DOI: 10.1007/s10508-016-0812-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Changes in Attractions and Social Determinants of Mental Health in Transgender Adults

Abstract: This study examined associations between changes in self-reported attractions and mental health in a community-based sample of self-identified transgender adults. Participants were purposively recruited in 2013 using bimodal sampling methods and completed a one-time survey. Multivariable logistic regression models estimated Adjusted Risk Ratios (aRR) and 95% Confidence Intervals (95% CI) to examine associations between changes in attractions and mental health outcomes (lifetime self-harm, suicide attempts, dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 66 publications
3
24
1
2
Order By: Relevance
“…[53,54] The overwhelming majority of non-binary respondents (98.4%) self-identified as having a sexual minority sexual orientation, which is also consistent with findings from other research. [11,32] This substantial overlap between non-binary gender and sexual minority status is intriguing and supports the conceptualization that "non-traditional" gender identities (i.e., outside the gender binary) and sexual orientation are distinct yet interrelated constructs. More research is needed to understand the terms non-binary people use to describe and identify their sexual orientation identity, as well as the processes of gender identity and sexual orientation identity development.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…[53,54] The overwhelming majority of non-binary respondents (98.4%) self-identified as having a sexual minority sexual orientation, which is also consistent with findings from other research. [11,32] This substantial overlap between non-binary gender and sexual minority status is intriguing and supports the conceptualization that "non-traditional" gender identities (i.e., outside the gender binary) and sexual orientation are distinct yet interrelated constructs. More research is needed to understand the terms non-binary people use to describe and identify their sexual orientation identity, as well as the processes of gender identity and sexual orientation identity development.…”
Section: Discussionmentioning
confidence: 67%
“…[19] Understanding gender differences in experiences of victimization and violence within the transgender community is critical, as these experiences have been linked to poor mental health in transgender populations. [16,32] Research shows that transgender individuals relative to cisgender individuals experience heightened levels of depression, anxiety, substance use, suicidality, and poor mental and overall self-rated health. [16,[33][34][35][36][37][38] The USTS reported that binary participants (49%) were more likely to report current serious psychological distress than binary participants (35%), yet were slightly less likely to report lifetime suicide attempts (43% binary vs. 39% non-binary).…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Women are more likely to experience suicide ideation and attempt compared with men, whereas men die by suicide approximately three times more often than women. 43,45 Results are more mixed within (primarily adult) TGNC samples, with some studies finding higher rates of suicide outcomes among participants who were younger 20,21,46 and assigned female at birth (AFAB) 20,25,28 and other studies failing to find these relationships. 3,5,15,23,25,47 Rates of suicide appear lowest in Hispanic and African American populations and highest in Native American populations 48 ; however, differences in suicide ideation and attempt are less clear, 49 including within the few studies of TGNC individuals that have examined racial/ethnic differences.…”
Section: Theories Of Suicidementioning
confidence: 99%
“…3,5,15,23,25,47 Rates of suicide appear lowest in Hispanic and African American populations and highest in Native American populations 48 ; however, differences in suicide ideation and attempt are less clear, 49 including within the few studies of TGNC individuals that have examined racial/ethnic differences. 3,10,20,25 Several studies of TGNC individuals have also linked lower socioeconomic status with higher rates of suicide ideation and/or attempt, 13,14,46 and one out of four studies found differences by sexual orientation, with all identities other than heterosexual associated with higher rates of suicide attempt. 3,7,21,46…”
Section: Theories Of Suicidementioning
confidence: 99%
“…In this cross-sectional study, individuals who reported changes in attractions during their lifetime were more likely than individuals not reporting changes in attractions to report negative mental health outcomes, such as self-harm, suicidality, and depression (Katz-Wise, Reisner, White Hughto, & Budge, 2017). However, changes in attractions after socially transitioning were not significantly associated with mental health outcomes.…”
mentioning
confidence: 99%